2019
DOI: 10.1038/s41598-019-46704-9
|View full text |Cite
|
Sign up to set email alerts
|

Elevated aerosol layer over South Asia worsens the Indian droughts

Abstract: Droughts have become more severe and recurrent over the Indian sub-continent during the second half of the twentieth century, leading to more severe hydro-climatic and socio-economic impacts over one of the most densely populated parts of the world. So far, droughts have mostly been connected to circulation changes concomitant with the abnormal warming over the Pacific Ocean, prevalently known as “El Niño”. Here, exploiting observational data sets and a series of dedicated sensitivity experiments, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 71 publications
1
43
0
Order By: Relevance
“…Our study contributes to deducing the source regions of emissions of precursors of ATAL particles at the Earth's surface and their transport pathways to the UTLS which is important to develop recommendations for regulations of anthropogenic surface emissions of ATAL precursors. In a recent study, Fadnavis et al (2019b) argue that further increasing industrial emissions in Asia will lead to a wider and thicker ATAL having the potential to amplify the severity of droughts in India. Severe droughts would have fatal consequences on agriculture on the Indian subcontinent and therefore would result in strong socio-economic impacts in one of the most densely populated parts of the world.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study contributes to deducing the source regions of emissions of precursors of ATAL particles at the Earth's surface and their transport pathways to the UTLS which is important to develop recommendations for regulations of anthropogenic surface emissions of ATAL precursors. In a recent study, Fadnavis et al (2019b) argue that further increasing industrial emissions in Asia will lead to a wider and thicker ATAL having the potential to amplify the severity of droughts in India. Severe droughts would have fatal consequences on agriculture on the Indian subcontinent and therefore would result in strong socio-economic impacts in one of the most densely populated parts of the world.…”
Section: Discussionmentioning
confidence: 99%
“…During El Niño, the ATAL is thicker and broader over the Indian region, resulting in a reduction of the solar flux and a surface cooling of about 1 K over North India. An elevated ATAL over South Asia exacerbates the severity of Indian droughts (Fadnavis et al, 2019b). The radiative forcing by the ATAL can further be enhanced by volcanic eruptions in the region; Fairlie et al (2014, Fig.…”
mentioning
confidence: 99%
“…the troposphere is significant (Fadnavis et al, 2019) in altering the incoming solar radiation. The western part of India, where dust is the primary contributor of aerosol loading, exhibits decreasing trend of DRF SFC driven by decreasing trend of dust aerosols in the last decade (Pandey et al, 2017).…”
Section: Regional Variability Of Drfmentioning
confidence: 99%
“…The tropopause temperature (CPT and LRT) on monthly scales particularly during July and August 2015 also discussed. To quantify the changes that happened within the ASMA region, 11 years (2005ASMA region, 11 years ( -2015 This is supported by a recent study reported by Fadnavis et al (2019). They showed weaker upward motions and deficient rainfall in the 2015 monsoon due to the strong El Niño conditions.…”
Section: Discussionmentioning
confidence: 77%
“…They reported that the ASMA forms earlier and stronger in the La Niña period that leads to greater equatorward transport of O3-rich air from the extra-tropics into the northern tropics than during El Niño periods. Very recently, Fadnavis et al (2019) reported higher concentrations of aerosol layers observed in the ATAL region during the El Niño period over the northern part of South Asia. However, the above-mentioned studies are mainly focused on changes in the ASMA with respect to ENSO on seasonal scales or mature stage of monsoon (combined mean of July and August) respectively.…”
Section: Introductionmentioning
confidence: 96%